Historical and Poetic Subcorpus: Semantic Markup of Old-Book Lexical Units (Eurasian Journal of Philology Science and Education, 2025)
The Akhmet Baitursynov Institute of Linguistics, within the framework of the National Corpus of the Kazakh Language (NCKL), is developing a “Historical-Poetic Subcorpus” that includes texts of folk oral literature from the 15th-19th centuries. One of the pressing issues arising in the formation of this large database is the necessity of creating a semantic markup of old literary lexical unit’s characteristic of the specified period. This is due to the fact that the works of folk oral literature of this time contain complex lexical units whose meanings are unfamiliar to the modern reader. In this regard, the aim of our research is to determine the meanings of obscure lexical units found in poetic lines and to select a semantic markup for them. To achieve this goal, the international experience in developing semantic markup will be initially considered. In particular, the experience of semantic markup in the national corpora of Russian, Tatar, and Bashkir languages will be studied. The structural characteristics of old literary words and the criteria for their selection for inclusion in the annotated database are examined. Special attention is paid to the algorithm for creating semantic markup and the functional capabilities of this approach. The results obtained can be used in the creation of educational and lexicographical resources, as well as in the interpretation of old literary words. The research contributes to an in-depth study of the historical development of the Kazakh language and its cultural heritage.Keywords: historical and poeticsubcorpus,old book vocabulary,samples of oralliterature,semanticmarkup.